Computational Analysis of Iron Corrosion Inhibition by Compounds in Rimbang Leaf Extract (Solanum torvum) Using the DFT Method - Jufri, Qory Sidwa; Emriadi; Imelda (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Iron is one of the most widely used metals in industry. This study was conducted on the performance of inhibitor compounds in rimbang leaf extract against iron corrosion based on several theoretical approaches. The method used is Density Functional Theory (DFT) with the basis set B3LYP/6-31G. The parameters obtained from the optimization results are EHOMO, ELUMO, dipole moment, and total energy so quantum chemical parameters were obtained in the form gap energy (Î”E), electronegativity (Ï‡), ionization potential (I), electron affinity (A), hardness (Î·), softness (Ïƒ), electrophilicity (Ï‰) and nucleophilicity (Îµ), adsorption energy and bond energy. The calculation results showed that fisetin, alpha tocopherol-beta-d-mannoside and benzene,1-(bromomethyl)-3-nitro- were the most effective inhibitor molecules compared to other compounds. The interaction of inhibitors with Fe (110) crystals seen from the adsorption energy (Eads) and binding energy (Ebinding) shows that among the three best compounds contained in the rimbang extract alpha tocopherol-beta-d-mannoside has the lowest bond energy of -200.13 kJ/mol and the Inh-Fe bond length value is 1.84 Ã…. The bond energy and bond length values show that the interaction between the inhibitor and the Fe molecule is a chemical interaction.